Towards Effective Macroprudential Policy Frameworks : An Assessment of Stylized Institutional Models - Nier, Erlend (IMF Working Papers; Working Paper ;, 2011)
A number of countries are reviewing their institutional arrangements for financial stability to support the development of a macroprudential policy function. In some cases, this involves a rethink of the appropriate institutional boundaries between central banks and financial regulatory agencies, or the setting up of dedicated policymaking committees. In others, efforts are underway to enhance cooperation within the existing institutional structure. Against this background, this paper provides basic guidance for the design of effective arrangements, in a manner that can provide a framework for country-specific advice. After reviewing briefly the main institutional elements of existing and emerging macroprudential policy frameworks across countries, the paper identifies stylized institutional models based on key features that distinguish institutional arrangements. It develops criteria to assess the effectiveness of models, examines the strengths and weaknesses of models against these criteria, and explores ways to improve existing setups. The paper finally distills lessons and sets out desired principles for effective macroprudential policy arrangements.